GEOCHEMISTRY OF QUATERNARY DEPOSITES OF KERCH STRAIT - PASLAVSKA, O.; SYDORENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of numerous chemical analysis and semiquantitative spectral analysis for different varieties of Strait of Kerch quaternary sediments in accordance with conventional stratigraphical structure are given.